Does basic education students know the importance of agroecology production systems for the conservation of biodiversity? (Research, Society and Development, 2020)
The perception of a basic education of the importance of agroecological agricultural systems for human and environmental health is fundamental for changes in consumption habits, the conservation of local biodiversity and long-term social transformation. We analyzed, by utilizing a questionnaire consisting of open and closed questions, the perceptions about agroecological and conventional agricultural production systems in 360 final students of basic education residing in nine Functional Planning Regions of southern Brazil. We used classification categories for answers within thematic axes, expressed in percentages and analyzed by means of Chi-square and Kruskal-Wallis tests. In general, students recognize agroecological systems as healthier for their families and for soil and water conservation, largely because they do not use agrochemicals. However, they demonstrated difficulties when arguing their importance for the conservation of biodiversity, ecosystems and for ensuring the food security of populations. Television was the main source of information related to agroecology, mainly for students residing in rural areas, thus pointing out shortcomings in basic education regarding the approach of the theme in schools. Our results show the need to build a complex network of knowledge and discussions on agroecological agricultural systems in basic education, involving changes in student perceptions, behaviors and sustainable choices.